Political information on social media and its impact on first-time voters among Malaysian youth - Soon, Christine Wei Ting (2023)
General Election 15 has been conducted recently on with the approved legal amendment on lowering the voting age from 21 to 18 years old. This present study aims to determine the perception of Malaysian youth on how they make use of political social media to learn about politics and decide their voting and identify the aspects that will be focused on by the Malaysian youth for the 15th General Election from the social media post. A thorough analysis of survey responses from a sample of young Malaysian voters, with an emphasis on those between the ages of 18 and 24, is included in the findings. The findings highlight the complexity of factors impacting the political behaviours of young voters, even while the anticipated linear association between concerns about political information and lesser political participation is not entirely supported by the data. The results show that these first-time voters display excitement and passion, which is consistent with the general trend of rising political consciousness among Malaysian youth.